Alignment of ordinal and quantitative species abundance and size indices for the detection of shifting baseline syndrome. Issue 4 (5th May 2021) - Lyver, Phil O'B.; Timoti, Puke; Richardson, Sarah J.; Gormley, Andrew M.
Abstract: Loss of knowledge about historical environmental conditions and species' abundances threatens how new generations potentially perceive their environment and take action. The intergenerational shift in perceptions of environmental thresholds is a phenomenon frequently termed shifting baseline syndrome (SBS). The goals of this study were (1) to determine relationships between ordinal scores (e.g., few, many) and quantitative measures (e.g., estimates of population size) used by members of a Māori community in New Zealand to score indicators for understanding the abundance of forest resources, and (2) to then analyze these relationships according to people's age to detect the effects of SBS and the rate that this shift was occurring for each indicator. We detected consistent relationships between the ordinal scores and quantitative measures for six forest indicators provided by community members. However, there was only a high degree of confidence about the direction of the age effect for three abundance indicators (Kererū [New Zealand Pigeon], Hemiphaga novaeseelandiae, 15% increase [CI = 5.1–27.1%] in flock size for any given ordinal category for each decade increase in age; long‐finned eel, Anguilla dieffenbachia, 30% decrease [CI = −45.1% to −11.3%] in the distance (m) walked along a riverbank between observations of an eel for any given ordinal category for each decade increase in age; and Australian brush‐tailed possum, Trichosurus vulpecula, 27% decrease [CI = −38.9% to −13.9%] in the distance (m) walked through forest between observations of possum sign for any given ordinal category for each decade increase in age), but the effect was statistically strong for all three. The decoupling of indigenous peoples and local communities (IPLC) from their traditional lands and biodiversity by an array of political, environmental, social and economic drivers and feedback mechanisms have contributed to and exacerbated the conditions for SBS. However, the protection of customary practices to engage with the environment, including the harvest of natural resources, community‐based environmental monitoring initiatives, and cultural immersion education programs offer opportunities for IPLC to mitigate the often deleterious effects of SBS.